Scale of Socio-emotional Competences - Rojas Aliga, Kiara Shalom (2019)
Objective: To determine the psychometric properties of the scale of socio-emotional skills (ECSE) for workersin public and private institutions in Lima Este. Maethods: The study was not experimental transversal design,further characterized by systematic, controlled, empirical and critical. Non-probability sampling was used for theconvenience of researchers, based on criteria previously established inclusion and exclusion, the sample consistedof 186 workers, between the ages of 21 and 65. The validation process of the test comprised an analysis of contentvalidity by judges and evaluation by psychometric assessment in one phase: pilot validation sample to determinethe reliability of the test through the analysis of difficulty items, item-test correlation, estimation of Cronbachand factor analysis. Results: As a result of exploratory factor analysis showed that the construct is comprised of2-dimensional competition emotional and social with 44.87% of the total variance and in turn by 5 sub dimensions(emotional awareness, emotional regulation, participatory capacity, empathy and dispute resolution); Cronbach'sα for the whole instrument was 0.793; also those items that meet the following requirements a) correlation wasretained item - larger sub 0.3, b) Cronbach alpha coefficient (to remove the item) equal to or less than the subdimension, c) in its dimension factorial saturation above 0.30. As a result of this analysis they were invalidated31 items, which were eliminated, leaving the instrument consisting of 28 items. Conclusion: The instrument haspsychometric properties of construct validity as well as a good level of reliability